Effect of Web Opening Location on Fatigue Assessment of H Section Steel Beams - Ahmed Elboghdady; Mohamed Dabaon; Nashwa Yossef; Mahmoud El-Boghdadi (Journal of Engineering Research - Egypt)
In the last decades, steel beams with web opening were used extensively as useful structural and architectural elements due to their many advantages. In this research, steel beams with web opening subjected to static loading were modelled using the multi-purpose finite element software ANSYS and the finite element results were compared with previous research. Then, steel beams with a single web opening subjected to fatigue loading were investigated numerically. The effect of changing the location of web opening on the fatigue assessment of H section steel beams with web opening was studied taking normal stress into account. It was clear that, normal stress fatigue life of the steel beams was affected significantly by changing web opening location along the beam span when compared to a beam with solid web while the beam span, opening size and steel section were kept constant. The most convenient location of web opening along the beam span was found to be at mid span.